The Financial Inclusion Landscape in the Asia-Pacific Region : A Dozen Key Findings - Jahan, Sarwat (IMF Working Papers; Working Paper ;, 2019)
Financial inclusion is a multidimensional concept and countries have chosen diverse methods of enhancing financial inclusion with varying degrees of results. The heterogeneity of financial inclusion is particularly striking in the Asia-Pacific region as member countries range from those that are at the cutting edge of financial technology to others that are aiming to provide access to basic financial services. The wide disparity is not only inter-country but also intra-country. The focus of this paper is to take stock of the current state of financial inclusion in the Asia-Pacific region by highlighting twelve stylized facts about the state of financial inclusion in these countries. The paper finds that the state of financial inclusion depends on several factors, but a holistic approach calibrated to specific country conditions may lead to greater financial inclusion.